WHAT IS INSIDE VIRAL BEAUTY VIDEO AND HOW PEOPLE REACT TO IT - Habibah Ramdhani, Fairuz
Social media influencer and viral video are two prominent marketing phenomena at the moment. In the business areas, social media influencers are meant to share the message to its audiences in the form of sponsored content. The wider the exposure, the better. Hence, creating a viral video, which can be defined as a video with an unusual number of viewers, is one of their ways to reach many audiences. The beauty industry is one of the numerous industries that approach its customers or audiences through Youtube influencer. The audiences have several choices to response to the video, such as by liking it or sharing it through social media or in real-life conversations. The behavioral decisions taken by the audiences are important to gauge the impact of the marketing video. Currently, there has not been any study regarding content elements contained in specifically beauty video and behavioral decisions following it. Based on the problem stated, this research aimed to: 1) Identify the content elements in viral beauty video, 2) Understand the correlation between content elements on viral beauty videos and behavioral decisions of its audiences, and 3) Comprehend the correlation between beauty influencer level and content element of viral beauty videos. There are two levels of social media influencers discussed in this research, which are mega influencers (Tasya Farasya, Rachel Goddard, and Ini Vindy) and middle-user influencers (Abel Cantika, Rahmawati Kekeyi Putri Cantikka, and Titan Tyra). Mega influencers are those who have more than 1,000,000 subscribers on Youtube, while middle-user influencers are those with 100,000 to 500,000 subscribers on Youtube. The mentioned levels of social media influencers were chosen because in Indonesia, big players in cosmetic industries are collaborating with them to get exposure. This research uses the top three most-viewed videos from each influencer. The sample videos must have the number of viewers for more than 100,000 to be said as a viral video. The framework used in this research is benchmarking nine elements of viral video from Tyler West’s research. Those nine elements are length-title, brevity, laughter, surprise, irony, minority people’s presence, music, youth, and talent. Several adjustments were done to fit the nature of beauty video, including the change of minority people’s presence into famous people’s presence. This research uses video-watching experiment to collect the data. Through questionnaires, the respondents were asked about their perception of viral element in sample videos and behavioral decision in the form of like and share that they would like to enact after watching sample videos. Proportion percentage, chi-square test, and marascuilo test were conducted to analyze the data. The result shows that despite having myriad number of viewers, viral beauty videos do not contain the same elements as other viral videos. Other than that, the elements do not have correlation with behavioral decision taken. However, there is a correlation between viral elements and level of influencer.